المفعول المطلق ودالالته في أحاديث األربعين النووية - Ummu-Hani Abas (Kulliyyah Bahasa Arab, UniSHAMS, 2024)
This research tries to study al- Al-Maf’ūl al-Mutlaq in the forty hadiths of Imam AnNawawi which represents a problem among students to understand deeply the meaning of Hadith . It aims to discuss alAl-Maf’ūl al-Mutlaq from syntactic side and to look deeply at the purposes and denotations from different ways of expressions. This study depends on the statistical and analytical methods of analysis where it gives it’s numeral statistics and tries to analyze the Al-Maf’ūl al-Mutlaq. Then, analyze them analytically according to the opinions of scholars in grammar, semantic and hadith. The results of this study shows that Al-Maf’ūl alMutlaq gives several meanings; To explain the type of mentioned ‘Āmil and emphasize it, to explain the number of the mentioned ‘āmil and emphasize it. Beside that, the al-Maf’ūl al-Mutlaq and with its deleted ‘āmil indicates emphasis and abbreviation.